STRATEGI PENCEGAHAN SPASME ARTERI RADIAL PADA PCI TRANSRADIAL: TINJAUAN LITERATUR SISTEMATIK - Mira Dwi Lantasary; Latifah; Indah Almaidah; Evi Nurhidayati; Afridayanti Siregar, Devi (Program Studi S1 Ilmu Keperawatan dan Ners IKBIS Surabaya, 2025)
Background: Radial artery spasm is a common complication in transradial PCI procedures that can hinder procedural success and increase patient risk. Therefore, preventing radial artery spasm is crucial to improving procedural outcomes. Objective: This systematic literature review aims to evaluate various strategies for preventing radial artery spasm during transradial PCI, including both pharmacological and non-pharmacological interventions. Methods: This systematic literature review follows the PRISMA guidelines, with article searches conducted in three major databases (PubMed, Scopus, Google Scholar) for studies published between 2016 and 2025. Inclusion criteria were studies addressing the prevention of radial artery spasm and the interventions used to prevent such complications. Results: The use of spasmolytic agents, such as nitroglycerin and verapamil, has proven effective in reducing radial artery spasm. On the other hand, local heating with infrared emitters also shows potential for improving artery diameter and reducing procedure duration, although its effects are more gradual. A multimodal approach combining pharmacological and non-pharmacological therapies provides the best results in preventing radial artery spasm. Conclusion: Preventing radial artery spasm in transradial PCI requires a comprehensive approach, combining both pharmacological and non-pharmacological therapies. Local heating can be an effective additional option; however, further research is needed to validate long-term outcomes and improve transradial PCI results.